Seasonal Variation in Hydrological Parameters of Krishnagiri Dam, Krishnagiri District, Tamil Nadu, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In this present study, hydrobiological characteristic features of the Krishnagiri reservoir Dam, the dates for the present study were collected from 3 sampling stations for the period of 6 months in both premonsoon and monsoon seasons. Physico-chemical factors like pH, temperature, EC, alkalinity, hardness, nutrients PO4, NO3, SiO3, TDS and heavy metal sediments were estimated by the standard methods. Total hardness and TDS, EC, Cl and Alkalinity showed higher values than the other parameters estimated in the study area.